The State’s Role in Recovering and Developing the Private Sector in Vietnam in the COVID-19 Pandemic - Anh, Do Vu Phuong; Duc, Do Minh; Nguyen, To The (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The COVID-19 pandemic has strongly hit the Vietnamese economy, including the private sector. Based on the analysis of the pandemic-caused impacts on this particular sector, the article evaluates the policies that Vietnam did implement in response to the COVID-19 pandemic in 2020 and 2021. It is found that the Government had issued a number of policies to support businesses such as investment capital, financial costs, labor, and employment... but there are still certain limitations. The article, therefore, proposes some recommendations to effectively implement those policies in the coming time.